Strategies of Islamic Education in Internalizing Islamic Values Through Intra and Extracurricular Learning - Siregar, Asrul; Clarisa, Aulia; Khairi, Sahara; Muliati, Indah (Sekolah Tinggi Agama Islam Sumatera Medan, 2025)
Islamic education plays a strategic role in shaping students’ Islamic character amid the challenges of globalization and moral value degradation. However, the internalization of Islamic values in educational practice still faces problems, particularly because intraculicular and extracurricular learning strategies are often implemented partially and separately. This study aims to systematically examine Islamic education strategies in internalizing Islamic values through intraculicular and extracurricular learning and to identify effective patterns of integration. The research employs a systematic literature review (SLR) method by analyzing relevant scholarly journal articles published over the last ten years from reputable databases. Data analysis was conducted using a thematic approach to synthesize strategies, theoretical frameworks, and empirical findings from previous studies. The results indicate that intraculicular learning plays a significant role in transforming and conceptualizing Islamic values, while extracurricular activities are effective in habituating and actualizing values through direct experience. The integration of both domains has been shown to produce stronger and more sustainable value internalization. These findings imply the need for holistic and integrated Islamic education policies and instructional designs to strengthen the formation of students’ Islamic character.